Bridging a Gap in Coherence: The Coordination of Comprehension Processes When Viewing Visual Narratives - Maverick E. Smith; John P. Hutson; Mi’Kayla Newell; Dimitri Wing-Paul; Kathryn S. McCarthy; Lester C. Loschky; Joseph P. Magliano (Vision, 2024)
Scene Perception and Event Comprehension Theory (SPECT) posits that understanding picture stories depends upon a coordination of two processes: (1) integrating new information into the current event model that is coherent with it (i.e., mapping) and (2) segmenting experiences into distinct event models (i.e., shifting). In two experiments, we investigated competing hypotheses regarding how viewers coordinate the mapping process of bridging inference generation and the shifting process of event segmentation by manipulating the presence/absence of Bridging Action pictures (i.e., creating coherence gaps) in wordless picture stories. The Computational Effort Hypothesis says that experiencing a coherence gap prompts event segmentation and the additional computational effort to generate bridging inferences. Thus, it predicted a positive relationship between event segmentation and explanations when Bridging Actions were absent. Alternatively, the Coherence Gap Resolution Hypothesis says that experiencing a coherence gap prompt generating a bridging inference to close the gap, which obviates segmentation. Thus, it predicted a negative relationship between event segmentation and the production of explanations. Replicating prior work, viewers were more likely to segment and generate explanations when Bridging Action pictures were absent than when they were present. Crucially, the relationship between explanations and segmentation was negative when Bridging Action pictures were absent, consistent with the Coherence Gap Resolution Hypothesis. Unexpectedly, the relationship was positive when Bridging Actions were present. The results are consistent with SPECT’s assumption that mapping and shifting processes are coordinated, but how they are coordinated depends upon the experience of a coherence gap.